Über die pleistozänen Ablagerungen im südlichen Afrika - Maarleveld, G. C. (ERDKUNDE, 1960)
An attempt is made to correlate some pleistocene deposits of South Africa by means of artifacts (table 1). For the correlation between pluvial stages of South Africa and glacial stages of Western Europe strandlines a. o. were used (Monastirian I and II). It appears that the end of the South African Chellean Acheullean and the beginning of the Fauresmith-culture comes within the Eemian, between Monastirian I and Monastirian II. The end of the Fauresmith-culture and the beginning of the South African Middle Stone Age Complex probably come within the Middle Würm. By means of artifacts found in aeolian deposits is shown that the climate in South Africa during the formation of the Monastirian I beach was very dry. From pedological data it appears furthermore that after formation of Monastirian II beach and before the Holocene (thus during the Würm-time) the climate was more humid than to-day. From this can be taken that humid periods in South Africa are synchronous with the glacial stages of Western Europe and besides that dry periodes are synchronous with the warm periods of the northern hemisphere. In South Africa the principal incision of the rivers and deposition of coarse material took place during the transition of a dry (warm) to a humid (cool) period. By this transition the sparse vegetation was affected which lasted untill vegetation had adjusted itself to the new cool and more humid conditions. Severe erosion was possible in the first place by sparse vegetation and besides influenced by increased precipitation. After adjustement of the vegetation principally sand and loam were deposited by the rivers.